The effect on the quality of life of patients using transurethral resection (TUR) in the treatment of patients with benign prostatic hyperplasia (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article presents the results of scientific studies conducted in various research institutes and clinics in the Russian Federation, Europe, the USA, and our country on patients of different ages suffering from benign prostatic hyperplasia. Specifically, it provides an analysis of the literature on research results regarding the epidemiology of prostatic hyperplasia, treatment methods, particularly surgical methods. Among the surgical procedures presented, information is given on the positive outcomes and impact on the quality of life of patients treated with the transurethral resection of the prostate method.